Q. 194.0( 6 Votes )

# Prove that

Answer :

=

=

=

Using the formula,

sinA + sinB = 2sin cos

sinA - sinB = 2cos sin

Rate this question :

How useful is this solution?

We strive to provide quality solutions. Please rate us to serve you better.

RELATED QUESTIONS :

If the sides a, b, c of a ∆ABC is in H.P., prove that are in H.P.

RD Sharma - MathematicsIn any triangle ABC, prove the following:

RD Sharma - Mathematics

In any triangle ABC, prove the following:

a cos A + b cos B + c cos C = 2b sin A sin C = 2c sin A sin B

RD Sharma - MathematicsIn any triangle ABC, prove the following:

a(sin B – sin C) + b(sin C – sin A) + c(sin A – sin B) = 0

RD Sharma - MathematicsIn any triangle ABC, prove the following:

RD Sharma - Mathematics

In any triangle ABC, prove the following:

a^{2} sin (B – C) = (b^{2} – c^{2}) sin A

In any triangle ABC, prove the following:

RD Sharma - Mathematics

In any triangle ABC, prove the following:

b cos B + c cos C = a cos (B – C)

RD Sharma - MathematicsIn any triangle ABC, prove the following:

RD Sharma - Mathematics